DI BALIK KEDEKATAN DENGAN HEWAN PELIHARAAN: PENGARUH PET ATTACHMENT TERHADAP LONELINESS PADA REMAJA AKHIR DI KOTA PADANG - Sabrina Azzahra; Hanny Rufaidah Damra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Loneliness has become an increasingly prevalent psychological issue among adolescents, particularly during the transition to adulthood. One factor that may help reduce loneliness is emotional attachment to pets. This study aims to examine the effect of pet attachment on loneliness among late adolescents in Padang. This research used a quantitative approach with a simple linear regression design. A total of 384 respondents aged 18–22 years participated in the study. Data were collected using the Lexington Attachment to Pets Scale (LAPS) and the UCLA Loneliness Scale. The results showed that pet attachment had a significant effect on loneliness (β = 0.533, p < 0.001). The coefficient of determination (R² = 0.285) indicated that pet attachment contributed 28.5% to loneliness, while the remaining 71.5% was influenced by other factors. These findings suggest that emotional attachment to pets can function as an alternative source of emotional support for late adolescents, potentially reducing feelings of loneliness. The study highlights the importance of considering human–animal relationships as part of psychological well-being among adolescents.